Evaluation of the applicability of the root water uptake model on alpine meadows and analysis of root water uptake characteristics - Deng, Bin; Weng, Baisha; Yan, Denghua; Xiao, Shangbin; Gong, Xiaoyan; Li, Wenwen; Li, Meng (Frontiers in Earth Science, 2022)
It is essential to quantify the rate of root water uptake (RWU) and characterize the variability of RWU, which benefits understanding the water use of alpine meadows and its response to environmental changes. In addition, model simulation is one of the feasible methods to obtain the RWU characteristics of alpine meadows. However, recent research on RWU models mainly focused on crops and trees, while barely on alpine meadows. Thus, it is of great significance to develop an RWU model applicable to alpine meadows, which can describe local plant water consumption processes. In this paper, we measured the distribution characteristics of root density and soil characteristics of alpine meadows in the Qinghai-Tibet Plateau (QTP) with prototype observation experiments. The root length density (RLD) of the wilting stage decreased by 16.2% on average compared to the re-greening stage, and the ability of root growth was poorer in the high altitude area. Based on the distribution characteristics of root length density (RLD) and the three soil resistance indexes (soil water potential, soil hydraulic diffusivity, and soil hydraulic conductivity), which have obvious impacts on RWU. The improved Feddes model, Selim-Iskandar model, and Molz-Remson model were selected to simulate the RWU in alpine meadows, which fully considered the above impact factors, but the applicability in alpine meadows was not discussed. The results showed that the model performance of the Selim-Iskandar model was better than the improved Feddes model and Molz-Remson model, and its simulation performance was improved by 44.76% and 22.16% compared to the improved Feddes model and Molz-Remson model, respectively. Based on the quantified RWU rate, the RWU characteristics showed that the top 50% of the rhizosphere was responsible for 72.65% of the water uptake of the entire rhizosphere. At the same time, the obvious difference in RWU rate in different phenological stages was obvious, showing that the RWU rate in the re-greening stage increased by 36.52% compared to that in the wilting stage. This study can provide technical support for a more accurate estimation of transpiration and water use efficiency in alpine meadows, and could provide theoretical support for the implementation of vegetation.